A sky-blue fluorescent small molecule for non-doped OLED using solution-processing. Issue 87 (20th September 2015) - Tang, Fu; Peng, Jinghong; Liu, Ronghua; Yao, Chuang; Xu, Xinjun; Li, Lidong
<x xml:space="preserve">Abstract</x> A sky-blue fluorescent small molecule was employed to fabricate the non-doped emissive layer of solution-processed OLED.